Pengaruh knowledge gap dan service quality terhadap digital financial service experience dengan internet usage sebagai moderator - Khoirotunnisa, Fani; Dewanti, Mentari Clara; Rosyanti, Daisy Marthina (Jurnal Ilmu Manajemen, 2024)
Digital transformation significantly impacts various industries, compelling businesses to enhance their digital presence. In the financial sector, traditional banks and technology companies like Goto, Shopee, and Traveloka are entering the market with digital financial services and are becoming strong competitors. With the growing number of companies offering digital financial services in Indonesia, businesses are increasingly focused on delivering high-quality services to improve customer satisfaction and user experience. This study investigates factors influencing the user experience of digital financial services. Using purposive sampling, the study gathered 112 valid responses from Indonesian users of these services. Findings reveal that knowledge gaps negatively affect user experience, as limited understanding hinders full utilisation of available features. Additionally, high-quality service, characterised by reliability, ease of use, and responsiveness, enhances user satisfaction and trust, leading to a more positive overall experience. However, the study found no moderating effect of internet usage on the relationship between knowledge gaps and service quality, suggesting that other factors may play a more significant role in this dynamic.